2021
DOI: 10.1002/adpr.202100131
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Analysis of Peripheral Reflection from a Photonic Ball

Abstract: Colloidal crystals with spherical shapes are called photonic balls, and their optical properties have been extensively studied because they can be applied as structurally colored pigments or colorimetric sensors. When a colloidal crystal consists of small colloidal particles, e.g., 250 nm in diameter, the (111) crystal planes of the face‐centered cubic lattice cause Bragg reflection, resulting in a brilliant structural color. However, in colloidal crystals that consist of larger particles, e.g., 400 nm in diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…These diffraction rings in the peripheral part of the concavities seem to be a shape-dependent phenomenon which, although weak, could be constantly observed. Similar diffraction rings were reported in the case of photonic balls-colloidal crystals by R. Ohnuki et al, [ 62 ] when they were observed using objectives with different numerical apertures. They considered that the rings are caused by the tilted planes and refraction at the spherical surface which causes reflection in a highly oblique direction.…”
Section: Resultssupporting
confidence: 86%
“…These diffraction rings in the peripheral part of the concavities seem to be a shape-dependent phenomenon which, although weak, could be constantly observed. Similar diffraction rings were reported in the case of photonic balls-colloidal crystals by R. Ohnuki et al, [ 62 ] when they were observed using objectives with different numerical apertures. They considered that the rings are caused by the tilted planes and refraction at the spherical surface which causes reflection in a highly oblique direction.…”
Section: Resultssupporting
confidence: 86%
“…This morphology is also typically observed for SPs prepared under wellcontrolled drying conditions in emulsion-based systems. [7,63,64] The corresponding interstitial pores arising from such an arrangement are fully interconnected via necks formed from touching particles. We also quantify the pore size distribution within individual SPs from the tomographic reconstructions by inscribing a sphere of the largest possible diameter in each pore (maximum sphere inscription, MSI), [65] as exemplarily shown in Figure 2g, taken from Video S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…However, photonic band gap calculations revealed that the band gap corresponding to Bragg diffraction from the ⟨100⟩ direction is closed, unlike the open band gap of the ⟨111⟩ direction. 9 Therefore, the tetrahedral unit in the center of Figure 4e appears dark. In the edge-ring pattern shown in Figure 4b, the green lines originate from the {111} plane of the outside-exposed faces of the five tetrahedra combined with refraction at the spherical surface.…”
Section: Structural Investigation Of Decahedral Colloidalmentioning
confidence: 99%
“…This method, proposed by Velev et al, is widely used in fundamental and applied research. Some of the prepared clusters exhibit shell-like stacks of hexagonally arranged particle layers beneath the spherical surface. These layers correspond to the (111) planes of the face-centered cubic (fcc) lattice, and this type of spherical cluster is called an onion-like structure because the stacked layers are similar to onion peels. Such onion-like spherical clusters, whose optical properties have been investigated comprehensively, are used in optical materials such as pigments, colorimetric sensors, and anticounterfeiting materials. …”
Section: Introductionmentioning
confidence: 99%